Canadian Society of Nephrology COVID-19 Rapid Response Team Home Dialysis Recommendations. (May 2020) - ,; Copland, Michael; Hemmett, Juliya; MacRae, Jennifer M.; McCormick, Brendan; McCormick, Michael; Qirjazi, Elena; Singh, Rajinder S.; Zimmerman, Deborah
Purpose of program: This paper will provide guidance on how to best manage patients with end-stage kidney disease who will be or are being treated with home dialysis during the COVID-19 pandemic. Sources of information: Program-specific documents, pre-existing, and related to COVID-19; documents from national and international kidney agencies; national and international webinars, including webinars that we hosted for input and feedback; with additional information from formal and informal review of published academic literature. Methods: Members of the Canadian Society of Nephrology (CSN) Board of Directors solicited a team of clinicians and administrators with expertise in home dialysis. Specific COVID-19-related themes in home dialysis were determined by the Canadian senior renal leaders community of practice, a group compromising medical and administrative leaders of provincial and health authority renal programs. We then developed consensus-based recommendations virtually by the CSN work-group with input from ethicists with nephrology training. The recommendations were further reviewed by community nephrologists and over a CSN-sponsored webinar, attended by 225 kidney health care professionals, for further peer input. The final consensus recommendations also incorporated review by the editors at the Canadian Journal of Kidney Health and Disease (CJKHD). Key findings: We identified 7 broad areas of home dialysis practice management that may be affected by the COVID-19 pandemic: (1) peritoneal dialysis catheter placement, (2) home dialysis training, (3) home dialysis management, (4) personal protective equipment, (5) product delivery, (6) minimizing direct health care provider and patient contact, and (7) assisted peritoneal dialysis in the community. We make specific suggestions and recommendations for each of these areas. Limitations: This suggestions and recommendations in this paper are expert opinion, and subject to the biases associated with this level of evidence. To expedite the publication of this work, a parallel review process was created that may not be as robust as standard arms' length peer-review processes. Implications: These recommendations are intended to provide the best care possible during a time of altered priorities and reduced resources.